Застосування елементів машинного навчання для генерації альтернатив в системах обслуговування клієнтів - Островерхов, М. О. (ХНУРЕ, 2023)
The article deals with the development and comparison of methods of using artificial intelligence in customer service systems. The relevance and requirements for information and software are substantiated. To implement the generation of alternatives, it is suggested to use the method of machine learning. ML.NET and Accord.NET are offered as the most popular framework and library for the C# programming language.